Equality and Abortion: Legitimating Women’s Experiences - Harding, Sarah (Columbia Journal of Gender and Law, 1992)
Since Roe v. Wade’ the abortion debate has been confined within an individual rights framework, formulated as a “right of privacy,” The proponents of such an individual rights-based approach argue that a woman should have the absolute right to control her own body and make her own reproductive choices uninhibited by the law. This argument rests on a belief in the inviolability of individual rights. The most legalistic and ex- treme version of this approach can be found in J.J. Thomson’s provocative piece in which she compares the situation of a pregnant woman to that of a good samaritan: just as the law does not require people to be good samaritans, neither should a pregnant woman be forced to give up her body to sustain the life of her fetus, regardless of the issue of fetal personhood. Thomson’s argument by no means fully characterizes the complexity of the pro-choice position, but it is based on the same fundamental concept: the absolute right to control one’s body. Both approaches locate a woman’s right to an abortion in the abstract realm of individual rights, in a concept which provides women with the freedom to decide but which fails to provide a basis for understanding, supporting, and implementing that decision.